Efektivitas pendekatan kontemporer dan teknologi edukasi dalam meningkatkan imunitas iman generasi z - Selvia, Gita (Maliki Interdisciplinary Journal, 2025)
Contemporary approaches and educational technology have become increasingly important in the context of the technological advancements of our time. Through contemporary approaches that adapt to the needs of the time and the use of educational technology, this aims to explore how Generation Z can gain a deeper understanding of Islamic faith concepts, thereby enhancing the spiritual resilience of Generation Z itself. This research method involves literature analysis and case studies to identify the benefits and challenges of implementing this approach. The findings of the research indicate that contemporary approaches and educational technology have great potential in strengthening the spiritual resilience of Generation Z by facilitating deeper understanding, wider access to information sources, and relevant digital skills development. However, challenges such as the development of appropriate materials, technology skills, and content control remain crucial in the effective implementation of this approach. The practical implications of this research are the importance of developing comprehensive and integrated strategies to integrate contemporary approaches and educational technology into the context of teaching Islamic faith to Generation Z in order to strengthen their spiritual resilience in facing the challenges of modern times.